The Design of Refrigerated Portable Fish Storage Prototype for Small Scale Fisheries - Muhammad Fatih Khairi; Sugeng Hari Wisudo; Dwi Putra Yuwandana; Fis Purwangka (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2024)
Indonesia as one of the biggest capitals with fisheries industry have more than 90% small-scale fisher spread around the nation. Sadly, in some region, small scale fishers not really implement the proper fish storing method due to the lack of space in their vessel and limited technology. This issue has led to a new idea to build a portable cooling fish storage specifically for small scale fisheries. The aim of this studies is to build and test the performance of prototype of portable fish storage. The method used is direct testing by doing several tests such as power consumption test, temperature decreasing rate, and cost simulation efficiently with some condition and variables. The performance test resulted that power consumption of portable refrigerated fish storage around 374,94 - 651,93 watt with temperature decreasing rate of 0,5 C/minutes. In cost simulation, the portable refrigerated can save up to 90% rather than a traditional fish storage.